Virtual echocardiography screening tool to differentiate hemodynamic profiles in pulmonary hypertension. (September 2020) - Vaidya, Anjali; Golbus, Jessica R.; Vedage, Natasha A.; Mazurek, Jeremy; Raza, Farhan; Forfia, Paul R.
This study validated a novel virtual echocardiography screening tool (VEST), which utilized routinely reported echocardiography parameters to predict hemodynamic profiles in pulmonary hypertension (PH) and identify PH due to pulmonary vascular disease (PHPVD ). Direct echocardiography imaging review has been shown to predict hemodynamic profiles in PH; however, routine use often overemphasizes Doppler-estimated pulmonary artery systolic pressure (PASPDE ), which lacks discriminatory power among hemodynamically varied PH subgroups. In patients with PH of varying subtypes at a tertiary referral center, reported echocardiographic findings needed for VEST, including left atrial size, E:e' and systolic interventricular septal flattening, were obtained. Receiver operating characteristic analyses assessed the predictive performance of VEST vs. PASPDE in identifying PHPVD, which was later confirmed by right heart catheterization. VEST demonstrated far superior discriminatory power than PASPDE in identifying PHPVD . A positive score was 80.0% sensitive and 75.6% specific for PHPVD with an area under the curve of 0.81. PASPDE exhibited poorer discriminatory power with an area under the curve of 0.56. VEST's strong discriminatory ability remained unchanged when validated in a second cohort from another tertiary center. We demonstrated that this novel VEST using three routine parameters that can be easily extracted from standard echocardiographic reports can successfully capture PH patients with a high likelihood of PHPVD . During the Covid-19 pandemic, when right heart catheterization and timely access to experts at accredited PH centers may have limited widespread availability, this may assist physicians to rapidly and remotely evaluate PH patients to ensure timely and appropriate care.